Rice land protection in a transitional economy: The case of Vietnam. Issue 4 (April 2021) - Chu, Long; Nguyen, Hoa-Thi-Minh; Kompas, Tom; Dang, Khoi; Bui, Trinh
Abstract: Agricultural land protection (ALP) is a standard policy response to a desire for food security. However, ALP may result in a misallocation of resources. Examining rice land policy in Vietnam, we determine the optimal level of rice land protected against other crops using a stochastic optimization model built on top of a general equilibrium framework, combined with sequential micro-simulations on household data. We find that converting part of protected rice land enhances economic efficiency. Nonetheless, the policy is relatively pro-rich, implying a trade-off between poverty reduction and economic efficiency, making some households in already poor areas worse off. Our approach can be applied to land-use planning generally, highlighting the relevant tradeoffs and the search for needed optimal land-use policies. Abstract : Farmland protection; Land policy; Rice; Vietnam; Inequality; Household welfare